Measurements of Energy Loss of Charded Particles Travelling in Crystalline Materials along the Channeling Directon - Kokkoris, M.; Vlastou, R.; Papadopoulos, C. T.; Aslanoglou, X.; Kossionides, S.; Grötzscheld, R. (HNPS Advances in Nuclear Physics, 2021)
A method for determining the energy loss and mean dechanneling distance of light charged particles traveling along a low index axis of a crystal in the backscattering geometry, is presented. The method is based on nuclear resonance reactions which act as a marker for the range in the backscattering spectra. Computer simulations based on the assumption of an exponential rate of dechanneling of the incoming particles in the crystalline material, are in good agreement with measured spectra. The results of applying this method to protons and alphas in crystals of Si, SiO2, SiC and MgO are discussed and possible improvements are indicated.